Strength Analysis of Driving Gearbox for High Speed EMU based on Workbench - Liu Jianliang; Fan Naize; Tian Huajun; Zhao Jiadong; Pei Bang; Guan He; Miao Weiwei; Xu Sen; Wu Anwei (Jixie chuandong)
Due to the current situation of Chinese high-speed motor train unit（EMU） gearbox monopolized by foreign for a long time,and facing the gearbox body cracking problems frequently,the aluminum alloy box body of high-speed EMU is redesigned.By using the three-dimensional modeling software Solid Works,the box body model is created,and the load calculation of the designed box body under two conditions of short circuit and startup is carried out separately.By using the finite element analysis software Workbench,the strength is analyzed,then the simulation test results verify the designed box body won’t appear plastic deformation and crack in both working conditions.According to the analysis results evaluated by TJ / JW064-2015 in startup conditions,to testify that the designed housing meet the requirement of train operation.The research has important reference value to the independent research and development of the high speed Emu gearbox.